Profitability determinants of financial services companies in Malaysia / Muhammad Aiman Hassani Abdul Nasir - Abdul Nasir, Muhammad Aiman Hassani (2022)
Profitability is one of the key indicators of a financial organization success. Using a data set spanning the years 2016 to 2020, this research examines the effects of internal drivers on financial services profitability using static panel data analysis on 4 companies listed on Bursa Malaysia. Equity management, asset management and organization size are all independent variable choosen for this study. In order to evaluate the relationship between explanatory factors and profitability, this study uses a Panel data model. This study backs up strong suggestions that internal elements should be considered when assessing a financial service company's. According to the findings, this study suggests that equity management is the most eligible factor that determine the profitability. Thus, more efficient of a company's equity management, the lower the risk obtaining profitability.